The Karasjok Supreme Court Judgment – and Its Significance for the Legal Survey in Finnmark - Ravna, Øyvind (Arctic Review on Law and Politics, 2024)
The Karasjok judgment was pronounced by the Supreme Court of Norway on 31 May 2024. By a narrow majority (6 to 5), the Supreme Court concluded that neither the population of the municipality of Karasjok as a whole, nor the Sámi part of it, have property rights to outlying fields in the municipality, as the landownership belongs to the Finnmark Estate (Finnmarkseiendommen/FeFo). The Supreme Court thus set aside the Finnmark Land Tribunal’s judgment, in which the conclusion was that the population’s property rights were established through immemorial usage. In this paper, I discuss the significance of this Grand Chamber judgment for the upcoming legal survey, including which scenarios can be expected.